FRI0083 Predictors for the discrepancy between patient's and evaluator's global assessment in rheumatoid arthritis: kurama cohort study. (23rd January 2014) - Furu, M.; Hashimoto, M.; Ito, H.; Fujii, T.; Terao, C.; Matsuda, S.; Mimori, T.
Abstract : Background: The Boolean based ACR/EULAR remission criterion is stricter than indexes based criteria. It is difficult to achieve the patient's global assessment (PGA) as the reason. We often observe the discrepancy between the PGA and the evaluator's global assessment (EGA) in clinical. Objectives: The purpose of this study is to investigate a reason of the discrepancy between the PGA and the EGA in Kyoto University Rheumatoid Arthritis Management Alliance (KURAMA) cohort. Methods: We chose the 370 of RA patients in our clinical cohort and assessed swollen joint count (SJC), tender joint count (TJC), CRP, ESR, PGA, EGA, pain score, stage, class, duration of RA, and health assessment questionnaire (HAQ). We analyzed the frequency of remission by the new ACR/EULAR remission criteria, and predictors of the discrepancy between the PGA and the EGA. Results: SDAS, CDAI and the Boolean based remission are achieved in 25.1%, 25.1%, and 17.3% of patients, respectively. As for fulfilling criterion in each component, SJC were 68.4%, TJC 71.6%, PGA 24.1% and CRP 83.5%. The average of PGA minus EGA (PGA-EGA) was 18mm. The PGA had correlation with pain score (r=0.84, p<0.0001), class (r=0.59, p<0.0001), HAQ (r=0.54, p<0.0001) and SJC(r=0.35, p<0.0001). The EGA had correlation with SJC (r=0.72, p<0.0001), TJC (r=0.64, p<0.0001), CRP (r=0.41, p<0.0001), PGA (r=0.39, p<0.0001), ESR (r=0.38, p<0.0001) and HAQ (r=0.38, p<0.0001). The PGA-EGA had correlation with pain score (r=0.81, p<0.0001), class (r=0.41, p<0.0001), HAQ (r=0.32, p<0.0001) and SJC (r=-0.18, p=0.0005). The main predictors for the PGA-EGA were class (p=0.002), pain score (p<0.0001), TJC (p<0.0001) and SJC (p<0.0001). Conclusions: The Boolean based remission criterion is strictest because it was difficult to achieve PGA in our clinical cohort. The most significant predictors for the discrepancy between the PGA and the EGA were pain, functional disability, TJC and SJC. Increased pain and functional disability led to discrepancy toward worse PGA, while increased TJC and SJC led to accordance toward worse EGA. Understanding the reasons for this discrepancy may help to facilitate management of RA. Disclosure of Interest: None Declared